Aberrant firing of replication origins potentially explains intragenic nonrecurrent rearrangements within genes, including the human DMD gene - Ankala, Arunkanth; Kohn, Jordan N.; Hegde, Anisha; Meka, Arjun; Ephrem, Chin Lip Hon; Askree, Syed H.; Bhide, Shruti; Hegde, Madhuri R. (Genome Research, 2012)
Non-allelic homologous recombination (NAHR), non-homologous end joining (NHEJ), and microhomology-mediated replication-dependent recombination (MMRDR) have all been put forward as mechanisms to explain DNA rearrangements associated with genomic disorders. However, many nonrecurrent rearrangements in humans remain unexplained. To further investigate the mutation mechanisms of these copy number variations (CNVs), we performed breakpoint mapping analysis for 62 clinical cases with intragenic deletions in the human DMD gene (50 cases) and other known disease-causing genes (one PCCB, one IVD, one DBT, three PAH, one STK11, one HEXB, three DBT, one HRPT1, and one EMD cases). While repetitive elements were found in only four individual cases, three involving DMD and one HEXB gene, microhomologies (2–10 bp) were observed at breakpoint junctions in 56% and insertions ranging from 1 to 48 bp were seen in 16 of the total 62 cases. Among these insertions, we observed evidence for tandem repetitions of short segments (5–20 bp) of reference sequence proximal to the breakpoints in six individual DMD cases (six repeats in one, four repeats in three, two repeats in one, and one repeat in one case), strongly indicating attempts by the replication machinery to surpass the stalled replication fork. We provide evidence of a novel template slippage event during replication rescue. With a deeper insight into the complex process of replication and its rescue during origin failure, brought forward by recent studies, we propose a hypothesis based on aberrant firing of replication origins to explain intragenic nonrecurrent rearrangements within genes, including the DMD gene.
10.1101/gr.123463.111